Living out nonconformity: Restoration ministers and their diaries - Colin HARRIS (E-REA)
In 1662 the Cavalier Parliament passed the Act of Uniformity to impose ecclesiastical conformity. Ministers were ordered to declare in front of their congregations their “unfeigned assent and consent” to the 1662 Book of Common Prayer. The act stipulated the deprivation of those who refused and three months imprisonment for those who continued to preach. Unable to comply, some changed profession and others took the risk of gathering separate churches. However, there were some who remained involved in the national church. This article first establishes the common characteristics of three nonconforming ministers which would have made it unlikely for them to conform. Secondly, it presents circumstances, relationships and personal qualities which helped these godly clergymen to continue ministering within the Church of England post 1662. Through their autobiographies and their diaries, this article analyses the personal narratives of Ralph Josselin of Earls Colne (Essex), Edmund Trench (Kent), and Oliver Heywood (Yorkshire).